PENGARUH PENGGUNAAN SMARTPHONE DAN E-LEARNING TERHADAP MOTIVASI BELAJAR SISWA PADA MATA PELAJARAN KEARSIPAN KELAS X OTKP DI SMKS KRIAN 2 SIDOARJO - Lussy Heavyndah; Durinda Puspasari (Laboratorium Program Studi Pendidikan Guru Sekolah Dasar, 2021)
The purposes of this research were to analyze the effect of smartphones on students' learning motivation, the effect of e-learning on students' learning motivation, and the combined effect of smartphones and e-learning on students' learning motivation in the record management subject for grade X OTKP at SMKS Krian 2 Sidoarjo. This study employed a quantitative research method. The samples were selected using a non-probability sampling technique with a total sampling method, involving all 86 grade X OTKP students at SMKS Krian 2 Sidoarjo. Data were collected through interviews and questionnaires, and the instruments were tested for validity and reliability. The data analysis included classical assumption tests, namely normality, multicollinearity, and heteroscedasticity tests, followed by hypothesis testing using multiple linear regression analysis. The results showed that smartphone use did not have a significant effect on students' learning motivation, while e-learning had a significant effect on students' learning motivation. Overall, smartphones and e-learning simultaneously had a significant effect on students' learning motivation in the record management subject at grade X OTKP of SMKS Krian 2 Sidoarjo.